Bibliometric Analysis of Islamic Market Mechanisms and Economic Justice in Global Sharia Economic Literature - Hafni Juniyanti; Rozalinda; Testru Hendra (Jeksyah: Islamic Economics Journal, 2026)
This study examines the thematic evolution and knowledge structure of research on Islamic market mechanisms and economic justice using a bibliometric approach integrated with a systematic literature review. A total of 78 Scopus-indexed publications from 2010 to 2025 were analyzed using PRISMA guidelines and VOSviewer to identify research trends, thematic clusters, and conceptual linkages. The findings reveal three dominant thematic clusters: (1) normative studies focusing on fair pricing, state intervention, and Islamic economic thought; (2) applied studies addressing market distortions, price stability, and Islamic financial inclusion; and (3) emerging themes related to sustainability, halal supply chains, and digital transformation. These results indicate a shift from conceptual discussions toward integration with contemporary economic challenges. Theoretically, this study contributes by clarifying the fragmented relationship between Islamic market mechanisms and economic justice and by mapping their position within the global research structure. Practically, the findings provide insights for policymakers and Islamic financial institutions in designing market systems that balance efficiency with distributive justice in line with maqāṣid al-sharī‘ah. This study also highlights future research opportunities in digital economy, regulatory frameworks, and the operationalization of Islamic market principles.